Potential of Mobile Applications in Prevention and Management of Cardio-Metabolic Diseases - Amutha Ramadas; Quek Kia Fatt (Public Health, 2016)
Background:The pervasive use of mobile computing and communication technologies in healthcare and public health is expanding even in low and middle income countries. Among all types of mobile phones, smartphones are a more recent development, with features such as computing capability, capacious memories, large screens and open operating systems. Besides delivering interventions and education programs, smart phone applications (apps) are also be-ing used to monitor progress and act as knowledge database. This review explored the current evidence of smart phone technology in prevention and management of cardio-metabolic dis-eases. Methods: A systematic search was done using the keywords [‘mobile Applications’ OR ‘tele-medicine’ OR ‘smartphone’] and [OR ‘cardiovascular’ OR ‘obes*’OR ‘metabolic syndrome’ OR diabetes OR dyslipid* OR hypertensi*], with limitation to ‘reviews’, English publications and the last 5 years. Databases searched include OVID MEDLINE, PUBMED, COCHRANE, CINAHL, SCOPUS and PROQUEST. The shortlisted reviews including meta-analysis, narra-tive and systematic reviews were qualitatively evaluated and findings were compared.Results: Twenty-six articles (n=26) comprised of apps inventory, narrative and systematic re-views were included in the following areas: nutrition (n=3), physical activity (n=4), tobacco smoking (n=1) and cardiovascular (n=1), type 2 diabetes (n=8) and obesity/weight loss (n=9).Conclusion: Although there is limited evidence, we can now see a shift towards development and investigation of existing and new apps in prevention and management of cardio-metabolic diseases. Future studies could explore the feasibility and long-term effectiveness of theory-supported apps that were developed with newest evidence.